Evaluation of thickness of cementum of periodontally diseased teeth of non-diabetic and type 2 diabetic patients: A scanning electron microscopy study - Radhika Gupta; Sushama R Galgali; Radhika M Bavle; Vidya Chandavarkar (Wolters Kluwer Medknow Publications, 2013)
Background: It is suggested that diabetes plays an important role in tooth loss. The periodontal structure and alveolar bone architecture in diabetics have revealed alterations. However, changes in cementum of diabetics with periodontal disease have not been evaluated adequately. Thus, the aim of the study is to evaluate and compare the thickness of cementum in diseased and healthy areas of roots of teeth with chronic periodontitis from non-diabetic (group I) and type 2 diabetic patients (group II). Materials and Methods: Thirty incisors indicated for extraction as a result of chronic periodontitis from group I and group II were selected. Measurements of Probing Depth (PD) and Clinical Attachment Loss (CAL) were taken prior to extractions. Area of the root surface above the CAL (notch) was designated as diseased, while the area below the CAL (notch) was designated as healthy. The extracted tooth samples were sectioned longitudinally and were evaluated by scanning electron microscopy (SEM). Descriptive statistical analysis was performed. Results of continuous measurements were presented as Mean ΁ SD. Results: The results showed that in both groups the thickness of cementum in diseased areas was lower in comparison to the thickness in healthy areas. The mean thickness of cementum in both healthy and diseased areas was higher in group II compared to group I, though the differences in both were not statistically significant. Conclusion: Within the limits of the present study, group II showed greater mean thickness of cementum in both healthy and diseased areas compared to group I, though the differences were not statistically significant.